Estimated of Shelf Life Salem Fish Crackers (Scomber japonicus) with Polypropylene Plastic Packaging and Metalized Plastic in Poklahsar Mina Sejahtera, Tangerang - Permadi, Aef; Afifah, Rufnia Ayu; Latifa, Dian; Hidayah, Nur; Salampessy, Randi B.S.; Handoko, Yudi Prasetyo; Maulani, Aghitia (Politeknik Kelautan dan Perikanan Karawang, 2022)
Information on the shelf life of food products is one of the information that must be included on the label of food product packaging. This study aims to obtain the estimated shelf life of fried salem fish cracker products (Scomber japonicus) packaged in polypropylene plastic and metalized plastic. Fried salem fish crackers (Scomber japonicus) are produced by Poklahsar